1999
DOI: 10.1017/s0950268899002149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological characterization of adenovirus genome type 7h isolated in Japan

Abstract: In 1996, three adenovirus type 7 (Ad7) strains were isolated from children with fever and upper respiratory diseases in Japan. Restriction endonucleases (REs) analysis and PCR amplification of the E3 7.7 kDa ORF revealed that these strains were genotype Ad7h and closely related to an Argentine Ad7h strain, which has been reported to be highly virulent and so far predominant only in South America. These strains showed weak cross-neutralizing activity and specific haemagglutination-inhibition activity to Ad3 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
3
28
0
1
Order By: Relevance
“…Twenty-two Ad7 strains isolated from 1987 to 1992 in Japan were Ad7d (22), and a recent countrywide epidemic of Ad7 in Japan during the period from 1995 to 1998 was attributed to Ad7d2 (23,35). Ad7h also has been recognized in Japan (9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Twenty-two Ad7 strains isolated from 1987 to 1992 in Japan were Ad7d (22), and a recent countrywide epidemic of Ad7 in Japan during the period from 1995 to 1998 was attributed to Ad7d2 (23,35). Ad7h also has been recognized in Japan (9).…”
Section: Discussionmentioning
confidence: 98%
“…strains obtained from the American Type Culture Collection (Manassas, Va.) and Ad3a, Ad7d (383), and Ad7d2 (Bal) reference strains obtained from the National Institute of Infectious Diseases, Tokyo, Japan, were also included. Japanese Ad7 strains 383 (Ad7d) and Bal (Ad7d2) have different BstEII restriction patterns (9,23).…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of this genome type remained restricted in countries of South Cone of South America (Argentina, Chile and Uruguay) until 1994, when it was identified in Southeast Brazil associated to a case of follicular conjunctivitis (Tanaka et al 2000). The circulation of this genome type outside of South America occurred in 1996 in Japan and in 1998 in Southeast of United States (Hashido et al 1999, Erdman et al 2000. The first identification of Ad7h in case of ARI in Brazil occurred in 1995 (Moura et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a variety of genome types can be identified by the restriction fragment length polymorphism (RFLP) technique (6). Temporal and geographical distributions of serotypes and genome types have been reported (2,5,(7)(8)(9)(10)(11)(12). It has also been indicated that the emergence or switching of serotypes and genome types can cause HAdV outbreaks (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although a higher virulence of HAdV7h was indicated during these outbreaks, there is no virological evidence to indicate increased virulence of HAdV7h. Outside of South America, HAdV7h was first identified in Japan in 1996 and then in the US in 1998 (5,9,23).…”
mentioning
confidence: 99%